Effects on cognition of 20 days of anodal trans-cranial Direct Current Stimulation (tDCS) over left dorsolateral-pre-frontal cortex (DLPFC) in patients affected by Mild Cognitive Impairment: A case-control study. Issue 1 (January 2019) - Fileccia, E.; Di Stasi, V.; Poda, R.; Rizzo, G.; Stanzani-Maserati, M.; Oppi, F.; Capellari, S.; Liguori, R.
Abstract : Mild Cognitive impairment (MCI) affects as long as 15% of population in the elderly. Trans-cranial direct current stimulation (tDCS) is a non invasive technique of neuro-modulation which has proved to influence performances on different cognitive domains. We investigate effects on cognition of 20 days anodal tDCS in 17 MCI patients compared to 17 matched MCI patients. Patients underwent neuropsychological evaluation at baseline and then were randomly assigned to anodal or sham group. tDCS protocol consisted in 20 min, 5 days per week (up to total 20 days), 2 mA anodal stimulation over left dorsolateral pre-frontal cortex (DLPFC). At the end of the last day of stimulation a second neuropsychological evaluation was performed. We compared baseline and after stimulation neuropsychological results in anodal vs sham groups using repeated ANOVA measures as statistical analysis test. At follow-up anodal group showed improvement in verbal episodic memory (p < 0.001) and figure naming test (p < 0.01), in a general index of cognitive function (Brief Mental Deterioration Battery) (p < 0.0001) and in a mood measurement test (Beck Depression Inventory) (p < 0.01). Anodal tCDS can be an useful low-cost and relative risk-free tool to improve cognitive symptoms in MCI.